El intercambio de la información relativa a la enseñanza de la ciencia y la tecnología en América Latina y el Caribe - Averbuj, E. (Enseñanza de las Ciencias. Revista de investigación y experiencias didácticas, 2006)
A summary of activities about the interchange of information concerning science teaching and technology in South America and the Caribbean region, is presented.